Engineered stem cells targeting multiple cell surface receptors in tumors. (21st August 2019) - Kavari, Sanam L.; Shah, Khalid
Abstract: Multiple stem cell types exhibit inherent tropism for cancer, and engineered stem cells have been used as therapeutic agents to specifically target cancer cells. Recently, stem cells have been engineered to target multiple surface receptors on tumor cells, as well as endothelial and immune cells in the tumor microenvironment. In this review, we discuss the rationales and strategies for developing multiple receptor-targeted stem cells, their mechanisms of action, and the promises and challenges they hold as cancer therapeutics. :